Proposed outcome measures for prospective clinical trials in juvenile idiopathic arthritis-associated uveitis: a consensus effort from the multinational interdisciplinary working group for uveitis in childhood - Heiligenhaus, Arnd; Mackensen, Friederike (Arthritis care & research, 2012)
Objective: To develop a set of core outcome measures for use in randomized controlled trials (RCTs) and longitudinal observational studies in juvenile idiopathic arthritis (JIA)-associated uveitis. Methods: The literature relating to outcome measures used in studies of uveitis in childhood and adolescence was reviewed. A set of core outcomes and domains was established using the Delphi process. This was reviewed by a representative multinational interdisciplinary working group. Nominal group technique consensus was reached on face and content validity of the range and content of the domains. The outcomes and the appropriate instruments for uveitis trials were adapted to the age ranges of patients with JIA-associated uveitis. Results: Consensus was reached that data should be reported at defined time points in longitudinal studies with patients stratified by prognostic markers. Visual acuity testing should be age appropriate. The severity of uveitis (measured as anterior chamber cell grade) and duration of active inflammation should be documented. Visually significant structural complications should be recorded and quantified with standard measures. The responses to treatment and corticosteroid-sparing effects of treatment should be documented. Patient-reported disease activity and age-specific uveitis-related quality of life should be reported using appropriate questionnaires. Conclusion: The proposed outcome measures in JIA-associated uveitis should aid in the standardization and comparison of future RCTs of the treatment regimens for this disease. The proposed outcome measures will be verified in a prospective validation study.